ANALISIS SWOT IMPLEMENTASI SERTIFIKASI HALAL PADA UMKM MAKANAN DAN MINUMAN KACAMATA MAQASHID SYARIAH - santi, mei; Eko Sujianto, Agus; Akhyak, Akhyak; Ashlihah, Ashlihah (JSE: Jurnal Sharia Economica, 2025)
Muslim consumer awareness of halal products in Indonesia continues to grow, yet the implementation of halal certification in food and beverage MSMEs still faces various challenges. This study aims to analyze the implementation of halal certification for MSMEs using the maqashid sharia approach and SWOT analysis. The research method used is qualitative descriptive-exploratory through in-depth interviews, observations, and documentation. The findings show that although the Free Halal Certification Program (SEHATI) and the OSS system ease access, MSME actors still face challenges related to digital literacy, understanding of procedures, and limited guidance. The SWOT analysis identifies strengths in religious motivation and regulatory support, weaknesses in technical-administrative aspects, opportunities from the growth of the global halal market, and threats in the form of digital inequality and low synergy between institutions. The maqashid sharia approach shows that digital halal certification contributes to the protection of religion, life, intellect, wealth, and business sustainability. This study highlights the importance of collaborative approaches and affirmative policies to enhance halal certification access for MSMEs, especially in peripheral areas.